Tooth wear and cleaning effect of an abrasive-free dentifrice - Jae-Hyun Ahn; Ji-Hye Kim; Won-Ho Ha; Yong-Duk Park (Elsevier, 2018)
Background/purpose: To evaluate the degree of wear on human teeth and the cleaning effect of abrasive-free dentifrice. A sodium pyrophosphate and cellulose-containing abrasive-free dentifrice and calcium carbonate-containing control dentifrice were evaluated. Materials and methods: Dentin and enamel specimens were subjected to 109,500 successive double strokes and 5480 double strokes in pH-cycling condition. A profilometer measured abrasion depth. The cleaning effect of dentifrices on artificial stain was evaluated by cleaning power (modified Stookey method) and by removal of colored stain on artificial tooth. Results: The experimental results were evaluated using Mann-Whitney U test. The abrasion depth in dentin specimens was 13.97-26.73 times smaller with abrasive-free dentifrice than with control dentifrice. The abrasion depth of enamel specimen was 2.17 ± 0.66 μm with control dentifrice. The values for abrasive-free dentifrice were too small to measure. In pH-cycling conditions using dentin specimens, abrasion depth was 14.28-19.00 times smaller with abrasive-free dentifrice than with control dentifrice. The cleaning power and removing effect of colored stain were statistically insignificant between abrasive-free dentifrice and control dentifrice (P > 0.05). Conclusion: The abrasive-free dentifrice was as effective as control dentifrice in its cleaning effect on artificial stain and can significantly reduce tooth wear more than control dentifrice. Keywords: abrasion, tooth wear, cleaning power, dentifrice